Time to Rt < 1 for COVID-19 public health lockdown measures. (9th December 2020) - Yung, C. F.; Saffari, E.; Liew, C.
Abstract: The epidemiological target of lockdowns is to drive down the effective reproduction number ( Rt ) to less than 1. A key unknown is the duration that lockdowns need to be in place to achieve this and which lockdown measures are effective. Daily number of laboratory confirmed community coronavirus 2019 cases were extracted from regular reports from the Ministry of Health Singapore from 20 March 2020 to 4 May 2020. We generated daily Rt to estimate the time needed for these public health lockdown measures to control the spread of severe acute respiratory syndrome coronavirus 2 as demonstrated by Rt < 1. It took about 14 days of nationwide lockdown for the Rt trend to change and start falling. The upper limit of the 95% confidence interval for time to Rt < 1 was day 15 of lockdown. We have shown that it is possible to start 'bending the Rt curve' about 2 weeks after implementation of specific lockdown measures with strict compliance.